The Murder of Mr. Wickham - Gray, Claudia (New York : Vintage Books, a division of Penguin Random House, LLC, 2022)
"After many years of happy marriage, Emma Knightley and her husband are throwing a house party, bringing together distant relatives and new acquaintances-not all of whom are well known to the Knightleys but are certainly beloved by every Jane Austen fan: Elizabeth and Fitzwilliam Darcy, Marianne and Colonel Brandon, Anne and Captain Wentworth, and Fanny and Edmund Bertram. Very much not invited is Mr. Wickham, whose latest financial scheme has netted him newfound wealth-and a broadening array of enemies. With his unexpected arrival, tempers flare and secrets are revealed, making it clear that everyone would be happier if Mr. Wickham got his comeuppance. Yet the Knightleys and their guests are all shocked when Wickham turns up murdered-except, of course, for the killer hidden in their midst. With everyone a suspect, it falls to the house party's two youngest guests to solve the mystery of who finally delivered to Wickham his just deserts: Juliet Tilney, the smart and resourceful daughter of Catherine and Henry Tilney, eager for adventure outside Northanger Abbey; and Jonathan Darcy, Elizabeth and Darcy's eldest son, whose adherence to propriety makes his father seem relaxed. In a tantalizing fusion of Austen and Christie, the unlikely pair must put aside their own poor first impressions-and uncover the guilty party before an innocent person is sentenced to hang."--
Keywords: Murder -- Fiction; England -- Fiction. -- Social life and customs -- 19th century; Detective and mystery fiction; Historical fiction